2005
DOI: 10.2188/jea.15.155
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Health as Related to Income, Socio-economic Status, Lifestyle, and Social Support Factors in a Middle-aged Japanese

Abstract: BACKGROUND: Few studies have examined the association of perceived health with socio-economic status, especially income, and social isolation and support in Japan. The purpose of this study is to clarify the associations among perceived health, lifestyle, and socio-economic status, as well as social isolation and support factors, in middle-aged and elderly Japanese. METHODS: Subjects were 9,650 participants aged 47-77 years who completed a self-administered questionnaire in 2000 in the second survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 36 publications
6
50
0
Order By: Relevance
“…We used current smoking and self-rated health statuses as health variables, because they were shown to strongly correlate with socioeconomic position in previous studies of the Japanese population. 14,[20][21][22]31,32 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used current smoking and self-rated health statuses as health variables, because they were shown to strongly correlate with socioeconomic position in previous studies of the Japanese population. 14,[20][21][22]31,32 …”
Section: Discussionmentioning
confidence: 99%
“…Second, only two health variables were used, namely, smoking and self-rated health statuses, which are the most common variables strongly associated with socioeconomic indicators. [13][14][15][19][20][21][22]31,32 It is possible that other health variables show degrees of association with income indicators different from those in this study.…”
Section: Income Indicators In Health Inequalitymentioning
confidence: 99%
See 2 more Smart Citations
“…These previous studies reported socio-economic status, lifestyle factors, social support, and social network including family, friends, and social group membership as factors associated with perceived health [14][15][16]. Of these factors, social group membership was identified as a particularly important determinant of health for the elderly, intervention in which is an effective method of promoting health lifestyles among the elderly [17,18].…”
Section: Introductionmentioning
confidence: 99%